Técnicas moleculares para caracterização e conservação de plantas medicinais e aromáticas: uma revisão - Souza, D.c.l. (Sociedade Brasileira de Plantas Medicinais, 2015)
ABSTRACT The studies which aim on the characterization and conservation of the germplasm from medicinal and aromatic plant species have been frequent, due to the economic potential of these species. Therefore, different molecular markers are available in the market, and the selection of one or more markers requires knowledge of their properties and applications. This work aims to present a literature review about the main molecular techniques used in these studies.

RESUMO Os estudos que visam à caracterização e conservação de germoplasma de espécies de plantas medicinais e aromáticas vêm crescendo de forma expressiva frente ao potencial econômico dessas espécies. Para tanto, diferentes marcadores moleculares estão disponíveis no mercado, e a seleção de um ou mais marcadores requer o conhecimento de suas propriedades e aplicações. Este trabalho tem por objetivo apresentar uma revisão bibliográfica sobre as principais técnicas moleculares utilizadas nesses estudos.
Molecular techniques for characterization and conservation of medicinal and aromatic plants: a review.
Keywords: biotechnology; molecular markers; plant genetic resource; biotecnologia; marcadores moleculares; recursos genéticos vegetais